2018
DOI: 10.1007/s12520-017-0591-5
|View full text |Cite
|
Sign up to set email alerts
|

Clarity and brilliance: antimony in colourless natron glass explored using Roman glass found in Britain

Abstract: This paper discusses the development of Roman antimony decolourised natron glass, its dominance, and subsequent decline, using new trace element data for colourless glass found in Britain. Experimental glasses are used to investigate the influence of different proportions of raw materials (particularly the ratio of natron to calcium carbonate) on the resulting transparency or opacity of glass when antimony is added. Focusing on the 1st to 3rd centuries AD, the study has found that (1) There are chronological d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 34 publications
(58 reference statements)
0
21
0
4
Order By: Relevance
“…In this assemblage, there is only one first to second century sample containing higher lead content (222 ppm). It has been suggested that earlier antimony glass tends to contain higher lead contents (Paynter 2006;Paynter and Jackson 2018), which goes well with the argument that different antimony sources would have been exploited through time (Lobo et al 2014). There are also variations in the lead content of the Sb glass from Bocholtz (Huisman et al 2009) suggesting that the Sb glass reaching the northwestern provinces was likely to be a product of the use of different antimony sources.…”
Section: Comparison Of the Compositional Groups At Oudenburg To Contementioning
confidence: 55%
See 1 more Smart Citation
“…In this assemblage, there is only one first to second century sample containing higher lead content (222 ppm). It has been suggested that earlier antimony glass tends to contain higher lead contents (Paynter 2006;Paynter and Jackson 2018), which goes well with the argument that different antimony sources would have been exploited through time (Lobo et al 2014). There are also variations in the lead content of the Sb glass from Bocholtz (Huisman et al 2009) suggesting that the Sb glass reaching the northwestern provinces was likely to be a product of the use of different antimony sources.…”
Section: Comparison Of the Compositional Groups At Oudenburg To Contementioning
confidence: 55%
“…Manganese and antimony have been found together in Roman glass (Gliozzo et al 2015;Jackson et al 2015). As their simultaneous presence is not necessary to decolour glass, this has been considered as a proof for mixing and recycling of different glass types (Braun 1983;Freestone 2015;Nenna et al 1997;Paynter and Jackson 2018). The study of glass recycling has gained importance in the last years as it is a crucial element to understand glass production patterns as well as ancient technology (Ceglia et al 2017;Freestone 2015;Jackson et al 2015;Paynter and Jackson 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Glass recycling appears to have been systematic and large-scale, in particular on the western fringes of the Roman Empire. This is reflected in the mixed composition of numerous glass assemblages and archaeological evidence from, for example, Roman Britain [63] and the seaborne trade of glass cullet [14,83]. Recycling and mixing of both end members of Roman glasses (Roman Sb & Mn) are less evident in areas close to the primary production sites in Egypt and the Levant.…”
Section: Discussionmentioning
confidence: 99%
“…White glasses with variable amounts of lead have been documented since the Hellenistic period, particularly in cameo and mosaic glass [58,61,62]. Even though it has been proposed that the lead may have been accidentally introduced with the antimony [58], recent experimental work has demonstrated that the presence of as little as 2% lead oxide modifies the viscosity and thus the workability of the glass, and facilitates the formation and dispersion of Ca 2 Sb 2 O 7 crystals during the melting process [59,63]. Elevated concentrations of lead were also found in some of the blue, turquoise, and grey tesserae from Noheda (1.00% < PbO < 2.13%).…”
Section: Antimony Compounds As Opacifiermentioning
confidence: 99%
See 1 more Smart Citation